Sequence Stratigraphy, Depositional Environment and Associated Lithofacies of Lacustrine Shale: A Case From the Upper Fourth Member of Shahejie Formation, Dongying Depression, Bohai Bay Basin - Li, Guiang; Lin, Chengyan; Dong, Chunmei; Ma, Pengjie; Du, Xinyu; Jiang, Long; Guo, Feng (Frontiers in Earth Science, 2022)
The lithofacies assemblages in the lacustrine shale of the Shahejie Formation in the Dongying Depression have different compositions due to the complex depositional climate, lake water conditions, and sediment supply. Hence, the lithofacies types and depositional conditions were analyzed based on parasequence division and lithofacies classification. According to gamma ray integrated prediction error filter analysis (INPEFA), handheld x-ray fluorescence (XRF) measurements, mineral composition, total organic carbon (TOC) content, and sedimentary structures, six parasequences (P1–P6 from bottom to top) were identified, and seven lithofacies are recognized: (1) organic-poor thin-bedded calcareous mudstone, (2) organic-poor laminated calcareous mudstone, (3) intermediate-organic laminated calcareous mudstone, (4) organic-rich laminated calcareous mudstone, (5) organic-rich calcareous shale, (6) organic-rich laminated carbonate-bearing mudstone, and (7) laminated silty mudstone. When the climate became warm and wet, the water level of the lake increased with a decrease in salinity, and the corresponding lithofacies assemblages in the P1 to P2 parasequences gradually changed from organic-poor thin-bedded and laminated calcareous mudstone to intermediate-organic and organic-rich calcareous shale. When the climate became humid and warmer, resulting in an increasing water level and terrigenous input, the lithofacies assemblages in the P3–P4 parasequences changed from organic-rich calcareous shale and laminated carbonate-bearing mudstone to laminated silty mudstone and calcareous mudstone. At the end, the climate became slightly drier and cooler with a decrease in the water level, and the P5 and P6 parasequences were dominated by intermediate-organic and organic-poor laminated calcareous mudstones. Through elemental analysis and lithofacies observation, we found that the redox conditions of the water may have changed over time. Among the parasequences, the water column of the P2 parasequence was mainly stratified by salinity, that of the P4 parasequence was mainly stratified by temperature, and that of the P3 parasequence was in transition. The synergistic effect of various factors played a key role in the enrichment of organic matter. This study highlights the depositional processes of the lithofacies assemblages in a lacustrine shale and contributes to the understanding of shale oil accumulation in lacustrine shale.